The role of tasks and group on group outcomes: differences be-tween Mexico and Spain - Osca, Amparo; Urien, Begoña; Rodrigo, María José (Anales de Psicología / Annals of Psychology, 2012)
This paper analyzes the differences in group processes and outcomes in a multinational company. The total sample consists of 363 employees: 121 Spanish (engaged in production tasks) and 242 Mexican workers (121 engaged in production tasks and 121 performing services tasks to the production line). According to our results Spanish’s perception of group processes (group cohesion, communication systems, orientation to the task and the effective management of conflict) and group results (satisfaction and effectiveness) is more positive than the perception of their Mexican counterparts. Besides, we have found several differences between the two Mexican samples, in group processes and group outputs in favor of those dedicated to providing services with more enriched tasks. Finally, we have studied the influence of the processes on the outputs from an exploratory perspective in each sample. The results show that satisfaction is explained by social interaction processes (communication and the effective management of conflict) in the three samples whereas to explain effectiveness we have to focus on the differences between the two countries.